Condenser Replacement Life Prediction Based on Condenser Back Pressure Loss Factor Using Simple Life Cycle Cost Management Method: Economic Life - Alam Eka Putra; Berkah Fajar Tamtomo Kiono; Marcelinus Christwardana (Green Publisher Indonesia, 2025)
Energy demand in Indonesia continues to increase, in line with the government's efforts to balance economic and population growth. In this context, the government-designed electricity supply policy prioritizes the use of coal as the main source of energy until 2050. Power plants face challenges in asset management, particularly in the replacement and maintenance of equipment such as condensers. This study aims to determine the economic life of condensers in Steam Power Plants (PLTU) with a capacity of 300 MW, as well as analyze the life cycle costs using the Simple Life Cycle Cost Management (LCCM) method. This method considers direct and indirect costs in decision-making related to equipment maintenance and replacement. The study also identified factors that affect the operational efficiency of the condenser, including backpressure and operational conditions. The results of the analysis show that careful monitoring and evaluation of the economic life of the condenser can optimize operating costs and improve the energy efficiency of the generation system. This study provides strategic recommendations for asset management in power generation, prioritizing a holistic approach in decision-making related to equipment maintenance and replacement. Thus, this research is expected to contribute to the development of more efficient energy policies in Indonesia.